Losses from top spoilage in corn and forage sorghum silages in horizontal silos - Dickerson, J.T.; Bolsen, K.K.; Brent, B.E.; Lin, C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Corn and forage sorghum silages were stored in small (simulated), farm-scale, bunker silos for 180 days, and dry matter (DM) and organic matter (OM) losses; fermentation characteristics; and temperatures were measured at 10, 20, and 30 inches from the original silage surface. Sealing the exposed surface significantly increased DM and OM recoveries in both crops, regardless of depth. Immediate sealing preserved more DM and OM than delayed sealing, particularly at the 10-in. depth. The unsealed silages from both crops maintained dramatically higher temperatures within the top 3 ft. than sealed silages. As expected, the unsealed silages deteriorated completely at 10- and 20-in. depths, and the delayed-seal, forage sorghum silage showed considerable deterioration at the 10-in. depth. The immediately sealed corn silages had better fermentation profiles than their forage sorghum counterparts. A mold inhibitor, Top Savor®, increased OM recovery by about 2 percent in the forage sorghum silage, but had no effect on corn silage. These results indicate that sealing (covering) silos immediately after filling greatly improves storage efficiency and silage quality in the top 3 ft.
Keywords: Beef; Silage; Top spoilage; Corn; Sorghum